Diagnostic Value of Glucose Transporter 1 (GLUT-1) Expression in Nested Variant of Urothelial Carcinoma - Ceren BOYACI; Kemal BEHZATOĞLU (Federation of Turkish Pathology Societies, 2019)
Objective: Nested variant is bland-looking but aggressive subtype of urothelial carcinoma (UC). Cases having significant muscle invasion do not cause problems but small and superficial biopsies may be challenging due to morphological similarities between nested variant urothelial carcinoma and benign urothelial lesions. Material and Method: We studied Glucose transporter 1 (GLUT-1), which is an integral membrane protein providing glucose pass through plasma membrane down its concentration gradient, to see if it is useful for the differential diagnosis. Twenty five cases of nested variant urothelial carcinoma and a control group consisting of 12 cases of cystitis glandularis, cystitis cystica and 4 cases of inverted papilloma were stained with GLUT-1 immunohistochemically. Membranous staining was scored on a scale of 0 to +3. Results: Eleven of 25 nested variant UC cases showed a score of 2 and 14 of them showed a score of 3 on immunostaining with GLUT-1. Two cases showed a score of 1 and 10 cases did not show any staining in the control group. Conclusion: Our results showed that GLUT-1 may be a helpful marker when morphological separation cannot be made between nested variant UC and benign urothelial leisons. We also think that anti-GLUT-1 antibody treatment may be an option in the targeted treatment of nested variant.